الأسرار البلاغية في القرآن الكريم سورة الصافات أنموذجا دراسة تحليلية بلاغية: Rhetorical Secrets in the Holy Qur’an Surah Al-Safaat as a Model Rhetorical Analytical Study - Monsuru Abdul Rasaq , Salaudeen; Abdalla Elgmati , Anas A (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
يتناول هذا البحث الأسرار البلاغية في سورة الصافات، واتبع الباحث فيه المنهجين، الوصفي والتحليلي، وهدفت الدراسة إلى بيان الأسرار البلاغية في سورة الصافات، من حيث الفرق بين الفصاحة والبلاغة عند القدامى والمحدثين، والضوابط البلاغية قبل نزول القرآن الكريم، والضوابط البلاغية بعد نزول القرآن الكريم، وتوصلت الدراسة إلى أن الأذواق تختلف في فهم الآيات القرآنية، الذي يستحسنه ذوقي، لا يستحسنه ذوقك، وأن هذه الأسرار البلاغية في سورة الصافت توضح الإحساس الوجداني بين الباحث والقارئ حتى تحصل المشاركة الوجدانية بينهما، وأن الآيات القرآنية التي حفلت بالأسرار البلاغية في سورة الصافات كانت همتها تتجه إلى تدريب الطلاب والدارسين على الانتفاع بالتناسق الفني بين طرفي الصور الفنية عقليا وشعوريا، فالتطبيق هو الثمرة الموجودة من كل علم، فلا قيمة لعلم من العلوم إلا إذا طبقت قواعده، وأن فهم الأسرار البلاغية في سورة الصافات؛ يجعلنا ندرك من غير شك مرونة اللسان العربي، وهذا مما يلمسه هذا البحث. This research deals with the rhetorical secrets in Surat Al-Saffat, and the researcher followed the two approaches, descriptive and analytical. And the study concluded that tastes differ in understanding the Qur’anic verses, which my taste prefers, but your tastes do not. Its mission is to train students and scholars to benefit from the artistic coordination between the two sides of the artistic images mentally and emotionally. The application is the existing fruit of every science. There is no value for a science of science unless its rules are applied, and understanding the rhetorical secrets in Surat Al-Saffat; It makes us realize without a doubt the flexibility of the Arabic tongue, and this is what this research touches.